HAK IMUNITAS ADVOKAT DALAM MENJALANKAN PROFESI - Mariske Myeke Tampi; Jeffry Pri; Priscilla Purnomoputri (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2018)
Responsibility as law enforcer requires an advocate to uphold law enforcement through client's assistance. In this regard, the profession of advocate itself is also as an officium nobile or the honorable one where the profession serves as a credence and a hope for the wider community to gain justice. Assistance to the client should not draw an advocate to justify all the wrongdoings of his client, but defend the rights of a suspect or defendant or other justice seekers in the face of the law, in short, against the seekers of justice, as the scope of the profession as an advocate is not limited to matters related to solely criminal law. This is the responsibility of an advocate as a law enforcer, not just a client defender. In carrying out his profession an advocate has a right of immunity that makes him immune to the law in order to enforce the law, as long as it is with compliance with the applicable provisions.